Ratification Of The Convention On Contracts For The International Sale Of Goods (CISG) To Improve Indonesian Business Actors Bargain Position In International Transaction Contracts - Mutiara Hermawati; Davilla Prawidya Azaria (DE LEGA LATA: JURNAL ILMU HUKUM, 2026)
Indonesian business actors are often in unfavorable bargaining positions on international contract transactions. Mainly is caused by inconsistency between KUHPerdata as the legal instrument and its implementation. This paper aims to explain how KUHPerdata and CISG determine the bargaining position then analyze CISG normatively as the best legal instrument option to improve Indonesian business actors and lift up its unfavorable position. Research method uses normative legal conduct by statute and comparative approaches. KUHPerdata and CISG are primary legal instruments in comparison while supported with the best practices in Vietnam and China. Result shows that KUHPerdata holds at least four crucial weaknesses which leads to an unfavorable position for its beared actors. On the other hand, CISG could overcome those weaknesses with the fundamental breach concept as its effective limit manifestation. By ratifying CISG and adopting the best practices in Vietnam and China would improve Indonesian beared actors bargaining position in international contract transactions.